ANALISIS KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI PERKEMBANGAN MODEL ATOM MELALUI PEMBELAJARAN BERBASIS MASALAH (PBL) - Afriyanto, Afriyanto; Haetami, Aceng; Marhadi, Muh. Alim (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2021)
Research has been carried out that aims to analyze the critical thinking skills of students  and  find  out  the  most  dominant  indicators  of  critical  thinking  skills  of students  after  the  implementation  of  the  Problem  Based  Learning  model.  This research was conducted in class X IPA SMA Negeri 1 Wawonii Utara. The sample of  this  study  was  21  students  of  class  X  science.  This  research  method  uses quantitative descriptive. The instruments used in this study are description tests and observation sheets. The results of data analysis show that the achievement of  students'  critical  thinking  skills  in  general  has  been  well  achieved.  The  most dominant  indicators  of  students'  critical  thinking  skills  in  the  high,  medium  and low  groups  are  the  same,  namely  the  interpretation  indicators  and  analysis indicators.